2018
DOI: 10.30607/kvj.424808
|View full text |Cite
|
Sign up to set email alerts
|

Süt Toplama Tanklarında Okratoksin A Varlığının Belirlenmesi

Abstract: Ochratoxin A (OTA) produced by several Aspergillus and Penicillium species is a mycotoxin that contaminates different foods and feedstuffs, including cereals, coffee beans, nuts, cocoa, pulses, beer, wine, spices, dried vine fruits, meat, milk. In humans and animals, OTA has been observed to be particularly nephrotoxic, hepatotoxic, immunotoxic, neurotoxic, embryotoxic, carcinogenic and teratogenic. Ochratoxin A is a stable molecule and can remain unchanged even after the processes applied. In this study, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Higher percentages of positive samples were found in a survey carried out in Turkey in 2017. OTA was detected at concentration levels ranging from 10 to 270 ng/L in 37 out of 40 cow's milk samples collected from milk collection tanks [71]. A subsequent study carried out in Turkey on 105 milk samples (35 raw, 35 pasteurized, and 35 UHT) showed an average level of an OTA concentration of 119 ± 19 ng/L [66].…”
Section: Discussionmentioning
confidence: 93%
“…Higher percentages of positive samples were found in a survey carried out in Turkey in 2017. OTA was detected at concentration levels ranging from 10 to 270 ng/L in 37 out of 40 cow's milk samples collected from milk collection tanks [71]. A subsequent study carried out in Turkey on 105 milk samples (35 raw, 35 pasteurized, and 35 UHT) showed an average level of an OTA concentration of 119 ± 19 ng/L [66].…”
Section: Discussionmentioning
confidence: 93%
“…The amount of OTA in this traditional beverage food is dependent on the amount of OTA in milk. The presence of OTA in the range of 2-270 ng/L was detected in 37 of the samples from 40 milk collection tanks in Burdur (Keyvan et al, 2018). In another study, an average of 119±9 ng/L OTA was found in 105 cow milk samples (Turkoglu & Keyvan, 2019).…”
Section: Ota In Milk and Dairy Productsmentioning
confidence: 89%
“…Sütlerin OTA miktarı ELISA yöntemi ile tespit edilmiştir [15,16]. Öncelikle süt örneklerinden 250 μl eppendorf tüpüne alınarak üzerine 750 μl metanol eklenmiştir.…”
Section: Metotunclassified